Evaluation of Er,Cr:YSGG Laser Effect on Microshear Bond Strength of a Self-Adhesive Flowable Composite in the Dentin of Permanent Molar: An In Vitro Study - Masoumeh Moslemi; Faezeh Fotouhi Ardakani; Fatemeh Javadi; Zahra Khalili Sadrabad; Zahra Shadkar; Mohammad Saeid Shadkar (Scientifica)
Aim and Background. Recently, new restorative materials such as self-adhesive flowable composites, because of their simple use and no need to bonding and etching, are considered important, particularly in pediatric dentistry. The aim of this study is to evaluate the effect of Er,Cr:YSGG laser on microshear bond strength of self-adhesive flowable composite on permanent teeth dentin in vitro. Material and Methods. In this experimental study, 40 dentin sections were prepared from healthy third molars and divided into two groups according to their surface preparation by Er,Cr:YSGG laser or without laser, only with silicon carbide paper. In each group, two groups of 10 teeth were treated with self-adhesive flowable composite (Dyad) and conventional flowable composite (acid etch and bonding). Samples were stored in normal saline and after 48 hours their bond strength was measured. The failure mode of samples was observed on stereomicroscope. In order to analyse the results, the one way ANOVA and Tukey’s test for multiple comparisons were used. Result. The maximum bond strength was related to conventional flowable composite with laser preparation group (24/21 Mpa). The lowest one was seen in Dyad composite without laser emitting (9/89 Mpa). The statistical difference between this two groups was significant (P value = 0/0038). The microshear bond strength differences between Dyad composite groups with laser preparation (mean = 16/427±1/79) and without laser preparation (mean = 12/85±1/90) were statistically significant too (P value = 0/01). Conclusion. Self-adhesive flowable composite has lower microshear bond strength than conventional flowable composite. Moreover, the laser irradiation as a surface treatment can improve this bond strength.